A novel hyperbolic slit contraction with constant strain rate for elongational rheology of polymer melts. (February 2019) - Luger, Hans-Jürgen; Löw-Baselli, Bernhard; Neunhäuserer, Andreas; Friesenbichler, Walter; Miethlinger, Jürgen
Abstract: We present an online rheometer for measuring the elongational viscosity of polymer melts and filled compounds that builds upon a recently presented design, which we modified to feature a novel hyperbolic two-part contraction between two slit sections. Our rheometer allows constant monitoring of both shear and elongational viscosity during extrusion. The hyperbolic slit contraction was designed to enable constant elongation rates along the die that are higher at the same flow rate than those of our previous model. Further, it allows pressure transducers to be incorporated directly into the flow channels, which prevents material from accumulating in pressure holes. We compare the results obtained with our new rheometer to those of other methods, including Cogswell analysis of High Pressure Capillary Rheometer (HPCR) data, measurement with a wedge-shaped slit die and measurement using a Sentmanat Extensional Rheometer (SER). Additionally, we report on the differences in elongational and shear flow behaviors of a linear low-density polyethylene, various polypropylene grades (e.g., for pipe, thermoforming and tape applications) and glass-fiber-reinforced polypropylenes. Elongational rheology is valuable in online quality control, since it is very sensitive, for instance, to differences in macromolecular structure or fiber-length distribution. Highlights: A two-part hyperbolic slit contraction for elongational rheology is proposed. The wall shape design enables constant elongation rates along the contraction. The presented rheometer allows online monitoring of both shear and elongational viscosity. For LDPE the results of the new elongational die are in good accordance with established methods. For PP fundamental differences between different characterization methods are obtained.